2019
DOI: 10.3390/ani9060366
|View full text |Cite
|
Sign up to set email alerts
|

The Visitor Effect on Zoo Animals: Implications and Opportunities for Zoo Animal Welfare

Abstract: Achieving and maintaining high standards of animal welfare is critical to the success of a modern zoo. Research has shown that an animal’s welfare is highly dependent on how various individual animal factors (e.g., species traits, genetics, temperament and previous experience) interact with environmental features (e.g., social grouping, enclosure design and sensory environment). One prominent feature of the zoo environment is the presence of visitors. Visitor contact can be unpredictable and intense, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
223
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(230 citation statements)
references
References 162 publications
(267 reference statements)
3
223
1
3
Order By: Relevance
“…It is possible that the presence of visitors exerted a negative effect on the behavior of captive A. paniscus in the PZGV since when visitation stopped or became reduced, the behaviors also stopped (personal observation). This situation has been previously reported in other studies, which observed a negative influence of zoo visitors on captive animals, mainly primates (CHAMOVE et al, 1988;SADE, 2013;SHERWEN;HEMSWORTH, 2019). We emphasize that studies considering this possible interference is necessary in the PZGV.…”
Section: Discussionsupporting
confidence: 82%
“…It is possible that the presence of visitors exerted a negative effect on the behavior of captive A. paniscus in the PZGV since when visitation stopped or became reduced, the behaviors also stopped (personal observation). This situation has been previously reported in other studies, which observed a negative influence of zoo visitors on captive animals, mainly primates (CHAMOVE et al, 1988;SADE, 2013;SHERWEN;HEMSWORTH, 2019). We emphasize that studies considering this possible interference is necessary in the PZGV.…”
Section: Discussionsupporting
confidence: 82%
“…With the exception of CU1, where animals were observed to be moving back and forth and the enclosure is located in close proximity to local settlements and roads, so stereotypic behavior was recorded during the application of the current protocol. According to [49], eye contact of visitors and wild animals in captivity can result in stress and stereotypic behavior. Following [34], fences at CUI should be covered with raffia in order to avoid frequent eye contact between the animals and the public.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the effect of visitors on zoo animals has expanded significantly in the past several years, providing increasing evidence of the various effects visitors can have on a range of zoo species [1]. However, the literature presents mixed findings, possibly because of a number of factors that may affect the response of zoo animals to visitors such as species-specific differences, individual animal characteristics, enclosure design and the nature and intensity of visitor-animal interactions [1,2]. As a result, the manner in which visitors affect zoo animals still remains unclear for many species, especially for a rarely studied taxa such as penguins [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the manner in which visitors affect zoo animals still remains unclear for many species, especially for a rarely studied taxa such as penguins [3]. Understanding the way visitors affect zoo animals is important because visitor contact can be unpredictable and intense, with zoo animals being exposed to a range of stimuli from visitors including auditory, visual, tactile, olfactory and vibratory stimuli [1,4]. These visitor stimuli may be perceived by zoo animals as, for example threatening or stimulating, and so understanding this can help identify characteristics of visitors, animals and/or enclosures that affect the nature of visitor contact and be subsequently managed accordingly by zoos [1,3].…”
Section: Introductionmentioning
confidence: 99%